Guidelines for performing skin tests with drugs in the investigation of cutaneous adverse drug reactions - Barbaud, A (2010)
Skin testing with a suspected drug has been reported to be helpful in determining the cause of cutaneous adverse drug reactions (CADR). Many isolated reports of positive drug skin tests are published, but without detailed information concerning the clinical features of the CADR and the method used in performing drug skin tests, such data are not very informative. A working party of the European Society of Contact Dermatitis (ESCD) for the study of skin testing in investigating cutaneous adverse drug reactions, has proposed the herein-reported guidelines for performing skin testing in CADR in order to standardize these procedures. In each reported case, the imputability of each drug taken at the onset of the CADR and a highly detailed description and characterization of the dermatitis need to be given. Drug skin tests are performed 6 weeks to 6 months after complete healing of the CADR. Drug patch tests are performed according to the methods used in patch testing in studying contact dermatitis. The commercialized form of the drug used by the patient is tested diluted at 30% pet. (pet.) and/or water (aq.). The pure drug is tested diluted at 10% in pet. or aq. In severe CADR, drug patch tests are performed at lower concentrations. It is also of value to test on the most affected site of the initial CADR. Drug prick tests are performed on the volar forearm skin with the commercialized form of the drug, but with sequential dilutions in cases of urticaria. Intradermal tests (IDT) are performed with sterile sequential dilutions (10-4, 10-3, 10-2, 10-1) of a pure sterile or an injectable form of the suspected drug with a small volume of 0.04 ml. Drug skin tests need to be read at 20 min and also later at D2 and D4 for patch tests, at D1 for prick tests and IDT. All these tests also need to be read at 1 week. The success of skin tests varies with the drug tested, with a high % of positive results, for example, with betalactam antibiotics, pristinamycin, carbamazepine and tetrazepam on patch testing, or with betalactam antibiotics and heparins on delayed readings of IDT. The results of drug skin tests also depend on the clinical features of the CADR. The use of appropriate control patients is necessary to avoid false-positive results.